Adenosine receptors differentially regulate type 2 cytokine production by IL‐33–activated bone marrow cells, ILC2s, and macrophages. Issue 2 (4th January 2018) - Csóka, Balázs; Németh, Zoltán H.; Duerr, Claudia U.; Fritz, Jörg H.; Pacher, Pál; Haskó, György
Abstract : Group 2 innate lymphoid cells (ILC2s) represent a rapid source of type 2 cytokines, such as IL‐5 and IL‐13, and play an important role in orchestrating type 2 immune response. Adenosine is an endogenous purine nucleoside, a catabolite of ATP that binds and activates ≥1 of 4 transmembrane G protein–coupled cell‐surface adenosine receptors (ARs)—A1, A2A, A2B, and A3 . Here, we studied the role of ARs in the regulation of cytokine production by ILC2s. We found that A2B ARs suppress the production of both IL‐5 and IL‐13 by ILC2s, whereas A2A ARs augment IL‐5 production and fail to affect IL‐13 release. Combined stimulation of all ARs led to the suppression of both IL‐5 and IL‐13 production, which indicated that A2B ARs dominate A2A ARs. Both pre‐ and post‐transcriptional processes may be involved in the AR modulation of ILC2 IL‐5 and IL‐13 production. Thus, we identify adenosine as a novel negative regulator of ILC2 activation.—Csóka, B., Németh, Z. H., Duerr, C. U., Fritz, J. H., Pacher, P., Haskó, G. Adenosine receptors differentially regulate type 2 cytokine production by IL‐33–activated bone marrow cells, ILC2s, and macrophages. FASEB J. 32, 829–837 (2018). www.fasebj.org